A C-Terminally Truncated Variant of Neurospora crassa VDAC Assembles Into a Partially Functional Form in the Mitochondrial Outer Membrane and Forms Multimers in vitro - Ferens, Fraser G.; Summers, William A. T.; Bharaj, Ameet; Stetefeld, Jörg; Court, Deborah A. (Frontiers in Physiology, 2021)
The voltage-dependent anion-selective channel (VDAC) is a porin in the mitochondrial outer membrane (MOM). Unlike bacterial porins, several mitochondrial β-barrels comprise an odd number of β-strands, as is the case for the 19-β-stranded VDAC. Previously, a variant of a VDAC from Neurospora crassa, VDAC-ΔC, lacking the predicted 19th β-strand, was found to form gated, anion-selective channels in artificial membranes. In vivo, the two C-terminal β-strands (β18 and β19) in VDAC form a β-hairpin necessary for import from the cytoplasm into mitochondria and the β-signal required for assembly in the mitochondrial outer membrane resides in β19. The current study demonstrated that the putative 18-stranded β-barrel formed by VDAC-ΔC can be imported and assembled in the MOM in vivo and can also partially rescue the phenotype associated with the deletion of VDAC from a strain of N. crassa. Furthermore, when expressed and purified from Escherichia coli, VDAC-ΔC can be folded into a β-strand-rich form in decyl-maltoside. Size exclusion chromatography (SEC) alone or combined with multi-angle light scattering (SEC-MALS) and analytical ultracentrifugation revealed that, unlike full-length VDACs, VDAC-ΔC can self-organize into dimers and higher order oligomers in the absence of sterol.